2017
DOI: 10.1177/0954406217710277
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics of planar linear array deployable structure based on scissor-like element with differently located revolute clearance joints

Abstract: This paper comprehensively investigates the parametric effects of differently located revolute clearance joints on the dynamic behavior of planar deployable structure based on scissor-like element. Considering the real physical mechanical joints, the normal and the tangential forces in the revolute clearance joints are respectively modeled using Flores contact-force model and LuGre friction model. The resulting forces and moments are embedded in the equations of motion of the scissor deployable structure for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…where r b Q and r j Q are the position vectors of potential contact points in the global coordinate systems, n j and n b are the normal vectors of the possible contact points (Li et al, 2018).…”
Section: Modeling Of Joint Clearance and Contact Force In Planar Deployable Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…where r b Q and r j Q are the position vectors of potential contact points in the global coordinate systems, n j and n b are the normal vectors of the possible contact points (Li et al, 2018).…”
Section: Modeling Of Joint Clearance and Contact Force In Planar Deployable Structuresmentioning
confidence: 99%
“…Muvengei et al (2012a) evaluated the effects of joint clearance at differently location on the dynamics of a slider-crank mechanism without considering friction. Li et al (2018) extended these insights to deployable structures considering clearance and friction. Flores et al (2007) analyzed the dynamic behavior of a slide-crank mechanism and a four-bar mechanism with different clearance size using the Poincaré map, concluding that when the points on the Poincaré map are scattered, the motion between the contacting bodies is irregular, and transition between continuous contact, free flight mode and collision mode.…”
Section: Introductionmentioning
confidence: 97%
“…Bai [3] studied the dynamic responses of satellite antenna dualaxis driving mechanism with two planar revolute clearance joints and developed an optimization method to reduce the undesirable vibrations due to impact forces in clearance joints. Li [4] investigated the effects of the number of clearance joints on the dynamic characteristics of planar deployable structure based on scissor-like element, and the results indicated that the motion in one revolute clearance joint will affect the motion in the other clearance joint. However, the combination motion modes between multi-clearance joints and some inner rules existing those modes are not revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical model of revolute clearance joint.As shown inFig. 1, the eccentricity vector which connects the centers of bearing and journal (O B and O J ) can be written as[3][4]: are the positional vectors of centers of bearing and journal in generalized coordinate system (XOY), respectively.…”
mentioning
confidence: 99%
“…On this basis, they further studied the dynamic characteristics as the location, clearance size, and number of the revolute joint varied. 14 Wang et al. 15 optimized geometry parameters, namely, the lock position, stiffness of hinges, and thickness of truss links, to improve the performance of a deployable support truss.…”
Section: Introductionmentioning
confidence: 99%